Advanced Thermal Management for PV Panels: Enhancing Efficiency with a Three‑Dimensional Pulsating Heat Pipe - Kargaran, Mahyar; Goshayeshi, Hamid Reza; Goshayeshi, Pooya (New Energy Exploitation and Application, 2025)
Harnessing solar energy represents a fundamental pillar of the global transition toward sustainable energy systems due to its abundance, renewability, and broad accessibility. Photovoltaic (PV) technology, in particular, has emerged as the most extensively deployed solution across residential, commercial, and utility‑scale applications. However, the relatively low energy conversion efficiency of PV modules remains a critical challenge, with elevated operating temperatures being one of the primary factors contributing to performance degradation. Excessive heat not only reduces instantaneous electrical output but also accelerates material aging, thereby shortening the service life of PV systems. Consequently, the development of efficient cooling strategies has attracted considerable research attention. In this study, an advanced passive thermal regulation approach based on three‑dimensional pulsating heat pipes (PHPs) was experimentally investigated. Two different inner diameters (2 mm and 3 mm) were designed, and their performance was evaluated using deionized water and graphene oxide (GO) nanofluid as working fluids. The results demonstrate that PHP integration can effectively reduce PV module surface temperatures, leading to notable improvements in electrical efficiency. The most significant enhancement was observed with GO nanofluid at a concentration of 0.8 g/L in 2 mm inner diameter PHPs, achieving up to a 3.2% increase in daily power generation compared with the baseline. Conversely, increasing the pipe diameter reduced the cooling effectiveness, underscoring the importance of geometric optimization and working‑fluid selection in the design of PHP‑assisted PV cooling systems.